2019
DOI: 10.1128/mra.01704-18
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequence of Streptococcus halitosis sp. nov., Isolated from the Dorsal Surface of the Tongue of a Patient with Halitosis

Abstract: Here, we report the draft genome of Streptococcus halitosis sp. nov. strain VT-4, a novel bacterium isolated from the dorsal part of the tongue of a patient with halitosis. The genome comprised 1,880,608 bp with a GC content of 41.0%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…We used NCBI Reference Sequence Database (RefSeq) genomes from the named Streptococcus species and unnamed Streptococcus “human microbial taxa” (HMT) in the eHOMD (http://www.homd.org). We also included genomes sequenced from human isolates if there was evidence of their presence in the human oral cavity (Bernardi et al., 2020; Huch et al., 2013; Shen et al., 2002; Tetz et al., 2019;). The Genome Taxonomy Database (GTDB) groups RefSeq genomes into clusters sharing ≥95% ANI (Parks et al., 2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used NCBI Reference Sequence Database (RefSeq) genomes from the named Streptococcus species and unnamed Streptococcus “human microbial taxa” (HMT) in the eHOMD (http://www.homd.org). We also included genomes sequenced from human isolates if there was evidence of their presence in the human oral cavity (Bernardi et al., 2020; Huch et al., 2013; Shen et al., 2002; Tetz et al., 2019;). The Genome Taxonomy Database (GTDB) groups RefSeq genomes into clusters sharing ≥95% ANI (Parks et al., 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Streptococcus "human microbial taxa" (HMT) in the eHOMD (http:// www.homd.org). We also included genomes sequenced from human isolates if there was evidence of their presence in the human oral cavity (Bernardi et al, 2020;Huch et al, 2013;Shen et al, 2002;Tetz et al, 2019;). The Genome Taxonomy Database (GTDB) groups…”
Section: Seq) Genomes From the Named Streptococcus Species And Unnamedmentioning
confidence: 99%
“…Some studies showed that the bacterial composition and diversity of the IOH group are different from those of the control group [8,9]. Previous studies have reported that bacteria to produce of volatile sulfur compounds (VSCs), such as Solobacterium moorei, Prophyromonas gingivalis, Treponema denticola, Prevotella intermedia, Streptococcus oralis, and Tannerella forsythia, are associated with IOH [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…We used RefSeq genomes from the named Streptococcus species and unnamed Streptococcus “human microbial taxa” (HMT) in the eHOMD (http://www.homd.org). We also included genomes sequenced from human isolates if there was evidence of their presence in the human oral cavity (Tetz et al 2019, Shen et al 2002, Huch et al 2013, Bernardi et al 2020). The GTDB groups RefSeq genomes into clusters sharing ≥ 95% ANI (Parks et al 2020).…”
Section: Methodsmentioning
confidence: 99%